Assessing the undergraduate medical students’ acceptance and barriers of community-based education in population and Puskesmas levels: A preliminary study - Matilda Stella Pradnya; Perigrinus H Sebong (Universitas Gadjah Mada, 2024)
Purpose: This study aims to identify aspects of acceptance and barriers to implementing community-based education (CBE) at the population and Puskesmas levels. Methods: A preliminary study was conducted in the Faculty of Medicine, Soegijapranata Catholic University, Semarang, in April 2024. Data were collected using a Likert-scale questionnaire, which surveyed 95 medical students participating in the CBE program at both the population and Puskesmas settings. Data analysis was carried out descriptively. Results: The distribution of respondents' experiential learning perceptions from the category